BubR1 is frequently repressed in acute myeloid leukemia and its re-expression sensitizes cells to antimitotic therapy - Schnerch, Dominik (Ferrata Storti Foundation, 2013)
Spindle poison-based therapy is of only limited benefit in acute myeloid leukemia while lymphoblastic leukemia/lymphoma responds well. In this study, we demonstrated that the spindle assembly checkpoint protein BubR1 was down-regulated in the vast majority of cases of acute myeloid leukemia whereas its expression was high in lymphoblastic cells. Correct function of the spindle assembly checkpoint is pivotal in mediating mitotic delay in response to spindle poisons. Mitotic delay by the spindle assembly checkpoint is achieved by inhibition of anaphase-promoting complex-dependent proteolysis of cyclin B and securin. We demonstrated a link between the repression of the spindle assembly checkpoint protein BubR1 in acute myeloid leukemia and the limited response to spindle poison. In accordance with its established role as an anaphase-promoting complex-inhibitor, we found that repression of BubR1 was associated with enhanced anaphase-promoting complex activity and cyclin B and securin degradation, which leads to premature sister-chromatid separation and failure to sustain a mitotic arrest. This suggests that repression of BubR1 in acute myeloid leukemia renders the spindle assembly checkpoint-mediated inhibition of the anaphase-promoting complex insufficient, which facilitates completion of mitosis in the presence of spindle poison. As both direct and BubR1-mediated restoration of cyclin B expression enhanced response to spindle poison, we propose that the downstream axis of the spindle assembly checkpoint is a promising target for tailored therapies for acute myeloid leukemia.